Forward and backward processes for INS compass alignment. (1st April 2015) - Gao, Wei; Lu, Baofeng; Yu, Chunyang
Abstract: Initial alignment is a crucial procedure for inertial navigation systems (INS). Both the alignment speed and alignment accuracy are important for INS; however, these two goals are difficult to achieve by using general methods at the same time. In order to resolve this contradictory issue, the forward and backward processes based method for INS alignment can be used. A new data processing method called forward and backward processes has been applied in INS alignment, based on that, a further research of forward and backward processes for compass alignment is done in this paper. The main contribution of this paper is to study whether the contradictory issue could be properly solved by using the forward and backward compass processes under the conditions of existing both the internal constant inertial sensor errors and external oscillatory errors caused by vehicle motions. Since the compass alignment is established based on classical control theory, the analysis of forward and backward compass processes is carried out using the error equations in frequency domain. The analysis and simulation results indicate that forward and backward processes for compass alignment can well solve the contradiction problem between alignment speed and accuracy only in the case of existing constant inertial sensor errors, namely the method is not applicable for existence of oscillatory errors. Highlights: Both the forward compass process and backward compass process are derived at length. The analysis of forward and backward compass processes is done in frequency domain. The analysis is focused on the influence of inertial sensor errors on misalignments. Feasibility analysis of this method is made in this paper. This method can solve the contradiction only in the case of constant sensor errors.